Prevalence, serotype, and antimicrobial resistance profiles of children infected with Salmonella in Guangzhou, southern China, 2016–2021 - Gao, Fei; Huang, Zhenting; Xiong, Zhile; Zheng, Hao; Deng, Qiulian; Zhong, Huamin; Zhu, Sufei; Long, Yan; Wang, Jielin (Frontiers in Pediatrics, 2023)
Abstract Purpose: Salmonella infection is a key global public health concern and has contributed to an increased economic burden on society. We investigated the epidemiological characteristics and antimicrobial resistance profiles of clinically isolated Salmonella strains in Guangzhou Women and Children's Medical Center. Patients and methods: This was a retrospective study of 1338 Salmonella strains collected from children in Guangzhou Women and Children's Medical Center between 2016 and 2021. Results: The results revealed that 1338 cases of Salmonella were mainly isolated from feces and blood samples. The age distribution was dominated by infants under 3 years old. The seasonal distribution was high in summer and autumn. 48 serotypes were detected, and S. Typhimurium (78.7%) was the predominant serogroup. The results of antimicrobial susceptibility showed that the highest resistance was observed in ampicillin (84.5%), while lower resistance was observed in piperacillin/tazobactam, cefoperazone/sulbactam and ciprofloxacin. The antimicrobial resistance rate of fecal isolates was higher than that of blood isolates. The five-year average detection rate of multi-drug resistant Salmonella was 8.5% (114/1338) and the MDR rate of S. Typhimurium was the lowest (6.9%; 73/1053). Conclusion: We concluded that antibacterial treatment should be carefully selected according to serotype and antimicrobial sensitivity results in children. Antimicrobial resistance monitoring for multi-drug resistant Salmonella is still required.